Identify Attacking Attempts through Logging on Websites and Database Systems by Machine Learning - Jameel Alwan, Hasan; Saad Ibrahim, Barakat; Hamid Shaker, Ahmed (International Journal of Engineering and Technology, 2018)
we will focus on the possibility of using and applying multiple technologies of information technology including, bank accounts, pattern recognition, follow_up data, and data mining. Improve the performance of these systems and techniques through new methods of learning and training, and thus improve the performance by reducing the costs of educational sources and the preservation, study and evaluation of the previous results through conversion to machines and machine learning technology.